2019
DOI: 10.1111/ijcp.13423
|View full text |Cite
|
Sign up to set email alerts
|

Blood eosinophils could be useful as a biomarker in chronic obstructive pulmonary disease exacerbations

Abstract: Summary IntroductionThe aim of analysing the usefulness of the blood eosinophil count (BEC) as a prognostic marker in exacerbations of patients with Chronic Obstructive Pulmonary Disease (COPD), evaluating its relationship with hospital mortality, the length of stay and the early and late re‐admissions. Materials and MethodsWe have carried out a retrospective study including all patients who required hospital admission from 1 January 2008 to 31 December 2009, with a diagnosis on hospital discharge of COPD exac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 44 publications
2
14
0
1
Order By: Relevance
“…Compatible with findings from previous studies, the eosinophilic group had significantly lower in-hospital and all-cause mortality compared to patients with nonelevated eosinophils [11,22,34,41,42]. Our results are, however, not in compliance with some authors that have reported no difference in the in-hospital mortality of eosinophilic and non-eosinophilic groups [5,6,32], these findings are, however, statistically not significant.…”
Section: All-cause Mortalitysupporting
confidence: 64%
See 3 more Smart Citations
“…Compatible with findings from previous studies, the eosinophilic group had significantly lower in-hospital and all-cause mortality compared to patients with nonelevated eosinophils [11,22,34,41,42]. Our results are, however, not in compliance with some authors that have reported no difference in the in-hospital mortality of eosinophilic and non-eosinophilic groups [5,6,32], these findings are, however, statistically not significant.…”
Section: All-cause Mortalitysupporting
confidence: 64%
“…The wide difference between these findings depend on many factors, such as stability of COPD, eosinophil measurement methods and different threshold values, among others. For instance, some studies have reported eosinophils as differential count by cells per μL [6,12,33], some by percentage [14,34,35] and others have used both [31,32,36]. The different measurements of eosinophils can, however, result in vastly different prevalence of high blood eosinophils in COPD patients.…”
Section: Clinical Severity and Long-term Prognosismentioning
confidence: 99%
See 2 more Smart Citations
“…Also, the data came from a single hospital and the results should not be generalized to other hospitals. Furthermore, other variable factors that may seem relevant to treatment failure, such as blood eosinophils, serum sodium, FEV1 <30% predicted, and treatment at discharge, were not obtained in this study [6,[29][30][31].…”
Section: Emergency Medicine Internationalmentioning
confidence: 99%